Two resistive switching regimes in thin film manganite memory devices on silicon - Rubi, Diego (2013)
Bipolar resistive switching in low cost n-Si/La2/3Ca1/3MnO3/M (M¼TiþCu) devices was investigated. For low SET compliance currents (CC), an interfacial-related resistive switching mechanism, associated to the migration of oxygen vacancies close to the manganite/metal interface, is operative. Simulations using the voltage enhanced oxygen vacancies drift model validate our experimental results. When further increasing the CC, we have observed the onset of a second, filamentary, resistive switching regime with a concomitant collapse of the ON/OFF ratio. We finally demonstrate that it is possible to delay the onset of the filamentary regime by controlling the film thickness.